Improvement of the ability to recover balance through versatile kinesthetic learning experiences - Matsuura, Yuki; Kokubu, Masahiro; Sakairi, Yosuke (Frontiers in Sports and Active Living, 2023)
The purpose of the present study was to compare learners’ movement variability while maintaining balance and the ability to recover balance using the kinesthetic-experiential learning (KEL) method of implicit learning and the model-mastery learning (MML) method of explicit learning. The participants were 29 healthy university students. They were randomly divided into two groups (KEL and MML). They were required to balance with both knees on an exercise ball. The balancing time and the ability to recover their balance were measured using motion capture. Results indicated that balancing time significantly improved for both learning methods. Regarding learners’ movements during maintaining balance, the learners maintained balance while moving in the KEL method, whereas they maintained balance keeping the entire body stationary in the MML method. Concerning the ability to recover, the KEL method improved the balance recovery ability more effectively than the MML method. Therefore, we concluded that using the KEL method at the initial stage of learning improves learners’ balance recovery ability and increases movement variability.